Struktur Peraturan Daerah Era Reformasi (Studi Perbandingan Peraturan Daerah tahun 2000-2006 di Kabupaten Brebes dan Kabupaten Pemalang) - Dwiyanto Indiahono (JKAP (Jurnal Kebijakan dan Administrasi Publik), 2008)
The local regulations in Indonesia develop fast in the reformation era. Many local regulations were produced by regency and city governments, so did in Brebes and Pemalang Regency. Local regulation structure is important to be examined in order to ger veluable information about tendency of the local government behavior which is reflected on the published local regulation (local public policy). Local government structure in Brebes and Pemalang show that the most dominant local regulation is the local regulation which is linked with organization and management as well as tax and retribution. This is show the enthusiasm of both regency to increase local government organization and management, also teh effort to increase regional pure income.